Contingency and opportunity: The first century of Hong Kong's public parks - Farris, Jonathan A. (International Planning History Society Proceedings, 2018)
The port city and British colony of Hong Kong had from its inception been characterized by a capitalist ethic and by dense settlement on land hemmed in between hills and sea. Preserving public land for general recreation was rarely prioritized as a primary government goal. Yet in Hong Kong’s first century (the 1840s to the 1940s) several public parks came into being and were resilient, while others were compromised. The history of these parks reveals no overall scheme, but responses to contingencies, each shaped by moments when public interest necessitated preserving open spaces and fostering green spaces for recreation.